Optimizing Leisure Agriculture by Analyzing Spatial Patterns and Tourists’ Perceptions: Evidence From Wuhan, China - Wang, Chengcheng; Wu, Shaohua; Yang, Wei; Bao, Haijun; Zhu, Jinxia; Wang, Xia (Frontiers in Environmental Science, 2022)
Leisure agriculture can meet the leisure needs of residents and promote farmers’ income, which is an important way to achieve rural revitalization. However, the unreasonable spatial patterns and weak competitiveness of leisure agriculture seriously restrict its sustainable development. This paper proposes a framework for optimizing leisure agriculture development, including spatial patterns analysis of leisure agriculture based on big data, quality analysis of leisure agriculture based on tourists’ perceptions, and strategies for optimizing leisure agriculture based on spatial patterns and tourists’ perceptions. Taking Wuhan city as an example, the results show that: 1) the main types of leisure agriculture are leisure farms, fishing, and picking gardens, showing an agglomerative distribution pattern; 2) considering tourists’ emotional perceptions, most comments are positive, and leisure farms should enhance the tourist experience; 3) tourists’ dissatisfaction mainly involves the environment, price, and travel, while product and service factors are relatively satisfactory; and 4) moderate agglomeration is beneficial to the quality of leisure agriculture, while excessive agglomeration has adverse effects. This study explores the development law of regional leisure agriculture, improves the relevant theoretical research system and methods, and provides decision-making references for promoting the development of leisure agriculture.